Rational Emotive Behavior Therapy for exercise: examining self-determined motivation, alongside readiness, confidence, and motivation to exercise - Martin J. Turner; Nick Frost; Leon Outar; Helen O'Connor; Renátó Tóth; László Tóth; László Tóth; Nanaki Chadha; Andrew G. Wood (Frontiers in Psychology, 2025)
IntroductionThe present paper aims to extend the scant research into REBT within an exercise population. A growing body of research supports the application of Rational Emotive Behaviour Therapy (REBT) theory and practice in exercise populations. However, very few research studies have tested the effects of REBT on exercise promotion. One vehicle through which REBT might facilitate exercise engagement is through mechanisms associated with self-determination theory (SDT).MethodsIn the current paper, using a staggered multiple-baseline across-participants single-case experimental design, REBT is applied with two non-exercising participants via video conferencing. We wanted to test the effects of REBT on participants' irrational beliefs, self-determined motivation, readiness, confidence, and motivation for positive change in exercise behavior.ResultsVisual and statistical analyses indicate that from pre to post REBT, participants reported reduced irrational beliefs, increased self-determined motivation, and increased readiness, confidence, and motivation for positive change. Findings are supported by social validation thematic analysis, in which positive changes in exercise behavior and motivation to exercise were revealed.DiscussionThe novelty of this paper is in its application of REBT (a specific form of CBT) to exercise participants, a rarely studied population in REBT literature. It is hoped that the paper helps the field to take another step towards the applicability of REBT in exercisers by adding to only three previous empirical works. The robust design and triangulation of analysis offers considerable value to the existing body of research suggesting that REBT is a promising one-to-one strategy for promoting exercise initiation in sedentary populations.